2019
DOI: 10.1021/acs.jpcc.9b04763
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised Exploration of MoS2 Nanocluster Configurations: Structures, Energetics, and Electronic Properties

Abstract: We propose an efficient method to explore the configuration space of nanoclusters by combining together ab initio molecular dynamics, metadynamics and data clustering algorithms. On one side, we employ collective variables sensitive to topological changes in the network of interatomic connections to map the configuration space; on the other, we introduce an automatic approach to select, in such space, representative structures to be optimized. In this way, we show that it is possible to sample thoroughly the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…We follow a previous work on the development of SPRINT ( S i ) coordinates (see the section S1.2 of the Supporting Information), which were originally established based on the use of spectral graph theory and have been used as a CV in the search for simple multistep reactions. , Nonetheless, given a reference atom in the system, we found that chemical information on its surrounding atoms that are too far away is missing and not included in the SPRINT coordinates of the reference atom, which may lead to unsatisfactory performance of SPRINT coordinates in the case of multiple-step or complicated reactions. A clear example supporting the existence of this problem is, for example, the case of intermediate or product molecules that are composed of atoms belonging to different reactant molecules.…”
mentioning
confidence: 99%
“…We follow a previous work on the development of SPRINT ( S i ) coordinates (see the section S1.2 of the Supporting Information), which were originally established based on the use of spectral graph theory and have been used as a CV in the search for simple multistep reactions. , Nonetheless, given a reference atom in the system, we found that chemical information on its surrounding atoms that are too far away is missing and not included in the SPRINT coordinates of the reference atom, which may lead to unsatisfactory performance of SPRINT coordinates in the case of multiple-step or complicated reactions. A clear example supporting the existence of this problem is, for example, the case of intermediate or product molecules that are composed of atoms belonging to different reactant molecules.…”
mentioning
confidence: 99%